An analysis of Helium resonant states in terms of entropy, information, complexity and entanglement measures (2014)
ABSTRACT: Shannon entropies and Fisher information calculated from one-particle density distributions and von Neumann and linear entropies (the latter two as a measure of entanglement) computed from the reduced oneparticle density matrix are analyzed for the 1,3Se,1,3 Po and 1,3De Rydberg series of He doubly excited states below the second ionization threshold. We find that both Fisher information and entanglement measures are able to discriminate resonances pertaining to different (K, T)A series.